La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 588/2014 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2014)
Ejemplar: Revista de la ESG. Año 92, no. 588 (sep.-dic. 2014). 187 p.